Tribology Research in Australia - Stachowiak, Gwidon (Japansese Society of Tribologists, 2007)
Australia is a country where the ancient culture of the Aborigines coexists with a modern culture in a young future-orientated multicultural society. Subconsciously, perhaps, this immersion in a situation where ancient problems require innovative new solutions has stirred the creativity and imagination of many Australian researchers in tribology. When compared with other countries of a similar population size, the Australian contribution to tribology is substantial. In this paper major achievements of Australian tribologists are presented.